EVALUASI KINERJA PROYEK PADA PRESERVASI JALAN DAN JEMBATAN PAREPARE–PINRANG–BATAS SULAWESI BARAT MENGGUNAKAN METODE EARNED VALUE MANAGEMENT (EVM) - Amelia; Ir Saleh; Inarmiwati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Cost and schedule performance evaluation is an essential aspect of construction project management to ensure that project implementation proceeds according to the planned objectives. This study aims to analyze the cost and schedule performance and estimate the project completion of the Parepare–Pinrang–West Sulawesi Border Road and Bridge Preservation Project using the Earned Value Management (EVM) method. The research employed a quantitative approach using primary data obtained through field observations and interviews, as well as secondary data including the Budget Plan (RAB), Time Schedule (S-Curve), weekly progress reports, and actual project cost reports. The analysis was conducted by calculating the indicators of Budgeted Cost of Work Scheduled (BCWS), Budgeted Cost of Work Performed (BCWP), Actual Cost of Work Performed (ACWP), Cost Performance Index (CPI), Schedule Performance Index (SPI), and the estimated project cost and completion time. The results indicate that up to the 12th week of project implementation, the Cost Variance (CV) was IDR 257,958,358, which is positive, with a Cost Performance Index (CPI) value of 1.056, indicating that the project was carried out efficiently and experienced cost savings (cost underrun). In terms of schedule performance, the project experienced fluctuations during several implementation periods; however, from the 9th to the 12th week, the schedule performance returned to a stable condition, indicating that the project is projected to be completed within the planned contract duration. The findings demonstrate that the Earned Value Management method provides a comprehensive evaluation of project cost and schedule performance and can serve as an effective tool for controlling and monitoring construction project implementation.